(untitled) (África, 1997)
A propos the publication of História Geral da África (General History of Africa), by UNESCO, and of the book A Enxada e a Lança (The Hoe and the Lance [Alberto da Costa e Silva: A enxada e a lança: A África antes dos portugueses. Rio de Janeiro, Nova Fronteira, 1992]), some considerations about African collective identity and regional specificities are discussed, in a time perspective, stressing the rupture of the transmission of the oral tradition and its deciphering by the several forms of art.